2019
DOI: 10.1111/bjep.12270
|View full text |Cite
|
Sign up to set email alerts
|

A latent growth curve analysis of precursor cognitive abilities and academic achievement

Abstract: Background Language‐based cognitive fitness describes the ability to carry out cognitive tasks with vigour and alertness, to learn, and to adapt. Aims The purpose of this research was to test the efficacy of a brain fitness training programme to better understand the role played by three precursor abilities for language‐based cognitive development—verbal reasoning, visual synthesis, and active analysis—and their impact on academic achievement. Sample The sample included 92 children from a private school design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Variations in learning and academic achievement levels among adolescents in the school stage can be attributed to differences in cognitive abilities ( Martins et al, 2016 ). Research suggested that cognitive abilities such as working memory, attention, and processing speed are crucial in facilitating learning and academic achievement ( Moxley-Paquette and Burkholder, 2020 ; Esposito and Bauer, 2022 ). For instance, individuals with higher working memory capacity can retain and manipulate more information in their minds, which facilitates the learning process ( Allen et al, 2021 ; Cotton and Ricker, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in learning and academic achievement levels among adolescents in the school stage can be attributed to differences in cognitive abilities ( Martins et al, 2016 ). Research suggested that cognitive abilities such as working memory, attention, and processing speed are crucial in facilitating learning and academic achievement ( Moxley-Paquette and Burkholder, 2020 ; Esposito and Bauer, 2022 ). For instance, individuals with higher working memory capacity can retain and manipulate more information in their minds, which facilitates the learning process ( Allen et al, 2021 ; Cotton and Ricker, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different factor loadings that were proportionate to the time intervals between adjacent waves were used to account for the unequal spacing of time between assessments (wave 1 = 0, wave 2 = 0.1, wave 3 = 0.6, wave 4 = 1.3). Multiple goodness of fit indices were used to assess model fit: chi-square (p( ) value greater than 0.05), comparative fit indices (CFI, greater than 0.90 [ 35 ]), Tucker-Lewis index (TLI, greater than 0.90 [ 35 ]), standardized root mean squared residual (SRMR, less than 0.08 [ 36 ], and root mean square error of approximation (RMSEA, less than 0.10 [ 37 ]). To test if model fit surpasses model complexity, the Akaike Information Criterion (AIC) and Bayesian Information Criterion (BIC) were utilized.…”
Section: Materials and Methodsmentioning
confidence: 99%